Pendampingan Pengembangan Soal IPA SMP Berbasis Asesmen Kompetensi Minimum (AKM) pada Guru SMP Swasta di Tulungagung - Setiani, Rahyu; Syafi'ah, Rohmatus (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Most science teachers, especially in private junior high schools in Tulungagung, have not implemented AKM-based assessments due to their limitations on the concept of AKM, resulting in difficulties in preparing AKM-based science questions. This community service activity is a real response to these needs with the aim that teachers can understand the concept of AKM and design questions that are by competency standards, especially in science learning. The stages of this Community Service Programme (PkM) include preparation, implementation, evaluation, and reporting. Preparation was carried out with an initial survey to identify the problems and needs of partners, the formation of the PkM team, and coordination between the PkM team and partners for programme planning. Implementation involved 11 junior high school science teachers from 8 private schools in Tulungagung, with activities consisting of explanation of concepts and practice of making questions. Evaluation was carried out by comparing the condition of partners before and after the activity, followed by an accountability report and scientific publication. Although the mentoring activities in the preparation of AKM questions have not achieved 100% success, some results can be noted. As many as 45% of participants were able to develop literacy-based junior high school science AKM questions. However, 55% of other participants still experienced difficulties in preparing AKM questions, both literacy and numeracy, due to the limited time for mentoring. In terms of enthusiasm, the mentoring activities can be said to be successful because 100% of the participants showed high enthusiasm and actively participated in the activities. They also actively sent their work results in the form of the preparation of AKM-based junior high school science questions, showing their readiness to apply these concepts in classroom learning.